Supporting leaders for school improvement through self-care and well-being - Carpenter, Bradley W.; Mahfouz, Julia; Robinson, Kerry (Educator) (Leadership for school improvement, 2023)
"School leadership instability is particularly problematic for scholars and practitioners concerned with PK-12 school improvement, as second only to teachers, campus leadership has been identified as a primary factor in students' academic success (Young et al., 2007). Yet, while principals play an indispensable role in students' academic success, the job has become considerably more stressful as the role of a school leader continues to evolve. Specifically, added responsibilities, increased work intensity, and the ever-present menace of high stakes accountability have intensified the stress levels encountered by today's school leaders (Carpenter & Brewer, 2012; Chaplain, 2001; Darmody & Smyth, 2016; Wang, et al., 2018). This intensification negatively impacts a school's teaching staff and its students, as the overall quality of the school experience can deteriorate if principals are unable to meet their potential due to the burnout and fatigue associated with chronic stress (Darmody & Smyth, 2016; Devos, et al., 2007). For principals to fully realize their ability to serve as catalysts for school improvement, they should be allowed to prioritize physical, mental, cognitive, and emotional health. Desired levels of wellbeing occur in the absence of chronic physical, social, psychological, emotional, economic, and cognitive distress (La Placa, et al., 2013). As authors in this volume demonstrate, many school leaders have commenced specific practices targeting cognitive, emotional, and behavioral wellbeing to cope with occupational stress and flourishing- or, at the very least, surviving in such a challenging environment. Among coping strategies leaders have adopted include mindfulness and other wellbeing interventions/strategies intended to facilitate healthier lifestyles, relieve stress, and improve personal resilience (Aviles & Dent, 2015; Mahfouz, 2018; Wells, 2015). Recently, there has been a call to consider educational leadership through a positive human flourishing lens. Research in this area focuses on integrating wellbeing practices in professional development programs for teachers and school administrators to highlight the positive effects of personal and collective wellbeing in schools (Cherkowski & Walker, 2014). For example, empirical studies have examined how incorporating mindfulness practice promotes positive adaptive skills, stress resilience, and social and emotional skills needed in a school environment (Abenavoli, et al., 2013; Benn, et al., 2012; Dvorkova et al., 2017; Jennings, 2015; Meiklejohn et al., 2012; Mahfouz et al., 2018). New understandings about the relationship between school administrators' wellbeing and school improvement efforts should ignite interest within the field. As such, this book's chapters are organized into four distinct sections that provide: (a) an overview of the field (Section I), (b) an empirical argument for why such research is essential (Section II), (c) wellbeing models to be considered for use in the PK-12 setting (Section III), and, (d) specific wellbeing practices and frameworks currently being in PK-12 (Section IV)"--